ANALISIS STRATEGI DIGITAL UNTUK PENINGKATAN KEUNGGULAN KOMPETITIF DALAM RANGKA IMPROVISASI KINERJA KEUANGAN UMKM - Nurmalasari, Nunik; Widarwati, Estu; Audina, Revina Nita; Apriandi, Devy Widya; Bismantara; Holle, Mohammad. H (IAIN Ambon, 2024)
Micro, Small and Medium Enterprises (MSMEs) have a major role in most economies in developing countries and their improvisation is determined by the Government's commitments. MSMEs have been impacted by the Covid 19 Pandemic so their financial performance had decreased due to the government policy in the imposition of restrictions on community activities (PPKM). MSMEs' financial performance can be determined by MSMEs' strategies and one of popular is the digital implementation in their business process for increasing the competitive advantage. This study aims to examine the role of digital strategy on financial performance that is mediated by competitive advantage in MSMEs. The sample selected owner MSMEs as respondents from some sub-districts of Subang. The questions are analyzed by the Method of Successive Interval (MSI), then processed with the regression model and Sobel test for testing the hypotheses. The results showed that MSME’s digital strategy has significant impact on incresing their competitive advantage. Furthermore, MSMEs’s financial performance depend on their quality of digital strategy and competitive advantage. The implication of finding is that MSMEs must be able to optimize their digital strategies for taking a lot of opportunities from their competitive advantages to improve the financial performance. Keywords: Strategy Digital, Competitive Advantage, Financial Performance, MSMEs